Assessing feasibility of resources at health facilities in Uganda to diagnose pregnancy and neonatal outcomes. Issue 2 (25th September 2018) - Stark, James H; Wool, Eve; Tran, Lena; Robinson, Elizabeth; Chemelski, Meaghan; Weibel, Daniel; Huang, Wan-Ting; Kochhar, Sonali; Hardy, Janet R; Bailey, Steven; Galiwango, Edward; Kajungu, Dan
Abstract: Background: Standardized case definitions for obstetric and neonatal outcomes were developed by the Global Alignment of Immunization Safety Assessment in Pregnancy (GAIA) project. These definitions can facilitate comparable assessment of maternal immunization safety surveillance and research. This study assessed the capabilities of health centers (HC) in Uganda to implement these definitions in a low income country, which has not been explored. Methods: Healthcare practitioners at 15 government-accredited health centers and one government-funded district hospital in the Iganga-Mayuge Health and Demographic Surveillance Site (IMHDSS) in Uganda were interviewed about the facility's clinical diagnostic and laboratory capabilities. Five obstetric and five neonatal case definitions were evaluated. Definitions with the highest diagnostic certainty were designated as level 1, while definitions that decreased in certainty were designated as level 2 or 4. HCs were evaluated on diagnostic and laboratory capabilities to apply the GAIA definitions. Results: Higher-level facilities in the IMHDSS demonstrated the ability to diagnose more specific levels of the GAIA obstetric and neonatal outcomes than lower-level facilities. Furthermore, for the neonatal outcome assessment, there was an increased ability to diagnose outcomes moving from GAIA level 1 to level 3. Conclusions: The ability of health centers to implement globally standardized definitions is promising for implementation of standardized data collection methods for global vaccine safety surveillance and research.